Adaptive decentralized control for switched nonlinear large-scale systems with quantized input signal. (February 2020) - Liu, Xuan; Zhai, Ding
Abstract: This paper deals with the adaptive fuzzy dynamic surface control (DSC) of a class of switched nonlinear large-scale systems whose input is quantized by a class of sector-bounded quantizers and the quantization parameters are allowed to be unknown. A new control law with hyperbolic tangent function form is introduced to develop a compensation mechanism to remove the restriction of the global Lipschitz condition. By designing switched first-order filters and switched adaptive laws for different subsystems, the switched controllers can not only show the switched systems changes sufficiently but also deal with the problem of "explosion of complexity". It is shown that the proposed control scheme can ensure that all the signals in the closed-loop system are bounded, and the tracking errors converge to a small neighborhood of the origin regardless of arbitrary switching. The simulation results demonstrate the validity and applicability of the proposed control scheme.